Sistem Pakar Diagnosa Penyakit pada Sapi Berbasis Android - Yulyanto M.Kom (FKOM UNIKU, 2019)
Handling reproductive disorders at the farm level is still lack due to the less information about the treatment of livestock which has a significant impact on decreasing of meat production. To reduce the impact of reproductive diseases, it is necessary to carry out early detection and treatment to prevent high losses and wider spread of disease. This article describes the application of an expert system that provides a means of consultation that uses an expert's reasoning process in solving complex problems regarding to cow reproductive health. In this study, the Tsukamoto Fuzzy method will be applied to help diagnosing the risk of disease in cattle based on six clinical symptoms. The result of this study is a mobile expert system that will conclude the risk level of endometriosis in cattle. This application is developed based on Android so that it is easy to use and it can be used by farmers to make a diagnosis independently. The result of this expert system testing indicates that this system can determine the level of endometritis risk of cow reproductive disease. Keywords: expert system, android based, fuzzy logic, cow disease